The earliest impact of restricted protein intake during pregnancy on heart development in male mouse offspring - Folguieri, Marina S.; Calsa, Bruno; Boer, Patricia Aline; Gontijo, José Antonio Rocha (Frontiers in Cell and Developmental Biology, 2025)
IntroductionMaternal protein restriction in animal models poses significant risks that lead to detrimental outcomes such as decreased birth weights, reduced nephron counts, neurological disorders, and increased arterial hypertension. Previous studies have shown that gestational protein deficiency is linked to reductions in cardiac mass, an increased presence of cardiac fibroblasts, and the development of fibrosis in both the left and right ventricles of adult rodents. This leads to the hypothesis that nutritional deprivation negatively impacts cellular proliferation mechanisms, ultimately resulting in a decrease in cell populations. AimsThe present study aims to elucidate the complex relationships among growth factor signaling, molecular expression profiles, and developmental pathways that underpin cardiac morphogenesis during the embryonic and fetal stages of development. We focus on the potentially harmful effects of maternal protein restriction on the cardiogenesis of the offspring. MethodsMethodologically, we analyzed the responses of female mice subjected to protein deficiency and evaluated the effects on their offspring, with a particular emphasis on early cardiac remodeling and key cellular pathways. Specifically, we analyzed cleaved caspase-3 as a marker for apoptosis, along with autophagy. Techniques employed include RT-qPCR, immunohistochemistry, and a transgenic model for direct quantification of autophagic flux. ResultsOur findings indicate that gestational protein restriction alters the expression profiles of genes associated with cardiac remodeling and increases the levels of apoptotic markers. In contrast, autophagic flux did not show significant alterations.ConclusionWe conclude that early protein restriction triggers a cascade of remodeling responses, including transient heart volume expansion accompanied by cardiomyocyte hypertrophy, which may progress towards fibrosis and metabolic stress. Autophagic flux was not significantly altered. We conclude that early protein restriction triggers a cascade of remodeling responses, including a transient heart volume expansion accompanied by cardiomyocyte hypertrophy, which has the potential to progress towards fibrosis and metabolic stress.